The Formation Of Interest In Physics In Schoolchildren Based On Didactic Approaches (Eurasian Journal of Physics,Chemistry and Mathematics, 2025)
This article explores modern didactic approaches that effectively engage pupils in the physics learning process. It discusses problem-based learning, interactive methods, project-based instruction, and the integration of digital technologies. Practical examples are used to demonstrate how these strategies enhance pupils’ critical thinking, inquiry skills, and interest in physics education.